SIMILAR DIFFERENCES OR DIFFERENT SIMILARITIES? ASSESSING FOOD SECURITY POLICIES IN GHANA AND BURKINA FASO THROUGH THE LENS OF SMALLHOLDER FARMERS - Santuah, N. F.; Abazaami, J.; Amikuzuno, J. (UDS International Journal of Development, 2022)
Policies designed to serve the needs of the poor often fail to elicit the right responses because policy makers and beneficiaries have different expectations. How this might manifest in different settings is not clear, particularly so among people with the same cultural ancestry but living in two different countries with different political systems. In this paper, we compared food security policies in Ghana and Burkina Faso from the perspective of Kasena/Gourunshi smallholder farmers. Data were gathered from three Case Studies, 13 focus groups and 28 key informants in two Districts in Ghana and two Communes in Burkina Faso using scientific and indigenous methodologies. The results showed that, in both Ghana and Burkina Faso smallholder farmers perceive food security policy as an externally funded programme dominated by maize to the detriment of their more nutritious traditional millets and sorghum. Food security policy has also altered smallholder farming systems and food security is now seen as business and politics, with little to do with food itself. We conclude that, under current food security policy, zero hunger by 2030 cannot be achieved without a paradigm shift from food security to food sovereignty which enables smallholder farmers maintain control over the farm enterprise and produce quality food. One pathway is to give the Ministries of Food and Agriculture in both countries a new focus by renaming them â€œMinistry of Agriculture and Food Sovereigntyâ€ (MAFoSo) or â€œle MinistÃ¨re de lâ€™Agriculture et de la SouverainetÃ© Alimentaire (MASA)â€. Keywords: Food Security, Food Sovereignty, Maize, Millets, Smallholder Farmers